Living hell : the dark side of the Civil War - Adams, Michael C. C., 1945- (The Johns Hopkins University Press, 2014)
Many Americans, argues Michael C.C. Adams, think of the Civil War as more glorious, less awful, than the reality. Tourists flock to battlefields, their perceptions of the war often shaped by reenactors who work hard for verisimilitude but who cannot ultimately simulate the horrors of war. In Living Hell, Adams uses the voices of actual participants on the firing line or in the hospital ward to create a virtual historical reenactment. Perhaps because the United States has not seen conventional war on its own soil since 1865, the collective memory has faded, so that we have sanitized and romanticized the experience of the Civil War. Living Hell presents a stark portrait of the human costs of the Civil War and gives readers a more accurate appreciation of its profound and lasting consequences. Adams examines the sharp contrast between the expectations of recruits versus the realities of dirt and exposure, poor diet, malnutrition, and disease. He describes the slaughter produced by close-order combat, the difficulties of cleaning up the battlefields-- often tens of thousands of dead and wounded--and the resulting psychological damage to survivors. Drawing extensively on letters and memoirs of individual soldiers, Adams assembles vivid accounts of the distress they faced daily. Providing a powerful counterpoint to Civil War glorification, Living Hell echoes William Tecumseh Sherman's comment that war is cruelty and cannot be refined.--Publisher information.